Gut microbial communities in chronic rhinosinusitis patients in response to 1,8-Cineol treatment - Simon Graspeuntner; Mathias Heidemann; Stephanie Jeschke; Mariia Lupatsii; Zuzana Penxova; Sven Künzel; Barbara Wollenberg; Anke Leichtle; Michael Ploch; Karl-Ludwig Bruchhage; Ralph Pries (Current Research in Microbial Sciences)
Background: Chronic rhinosinusitis (CRS) is a widespread inflammatory disease of the paranasal sinuses and the standard treatment includes surgery and the administration of corticosteroids or antibiotics. Antibiotics are well known to influence the microbial composition of the gut, including a reduced bacterial diversity and an increased antibiotic resistance. This underlines the need for alternative treatment approaches, especially regarding vulnerable patients such as children. Therefore, we evaluated the intestinal microbiota of CRS patients regarding plant-based anti-inflammatory monoterpene 1,8-Cineol, which is administered as the clinically approved drug Soledum® for the therapy of different inflammatory airway diseases including CRS. Methods: Microbiome analysis from stool samples was performed from 31 CRS patients before and after 1,8-Cineol administration using 16S rRNA gene next generation sequencing using dissimilarity-based and taxonomic approaches. Results: Data revealed elevated abundances of specific taxa including Bacteroides and Faecalibacterium as part of the physiologic gut microbial community and no overall disturbances in response to 1,8-Cineol treatment. Of note, abundances of intestinal Akkermansia muciniphila tend to increase during the course of 1,8-Cineol administration. Conclusion: Our data recommend 1,8-Cineol as a valuable addition to the current standard treatment of inflammatory diseases, without running the risk of profound changes of the gut microbial community.